Analisis Preferensi Konsumen Buah Jeruk Keprok Di Kabupaten Bojonegoro - Deviana Diah Probowati (Oryza : Jurnal Agribisnis dan Pertanian Berkelanjutan, 2016)
This study aims to determine the factors that influence consumer preferences in purchasing fruit of tangerine, citrus fruit attributes that are preferred by consumers in choosing fruits tangerines and marketing strategies that can be applied in marketing of fruit tangerine. Factors of consumer preferences on tangerine fruit analyzed in this study were sex, education level, occupation, age, income level and number of family members or dependents in the family. The results show that factor income effect on consumer preferences tangerine fruit in Bojonegoro. While the factors gender, education, age,jobs and the number of family members does not affect the consumer's preferences tangerine fruit in Bojonegoro. Based on the analysis Fishbein of research shows that consumer attitudes to attribute more importance tangerine fruit freshness and fruit flavors tangerine which has a value of 1.72 and 0.85 respectively. Meanwhile, the price factor is not a major consideration in selecting fruit consumers tangerines